Clinicopathological characteristics of patients with non-small-cell lung cancer who harbor EML4-ALK fusion gene: a meta-analysis. - Fengzhi Zhao; Meng Xu; Honcho Lei; Ziqi Zhou; Liang Wang; Ping Li; Jianfu Zhao; Penghui Hu (PLoS ONE)
Background A novel fusion gene of echinoderm microtubule-associated protein-like 4 (EML4) and anaplastic lymphoma kinase (ALK) has been recently identified in non-small-cell lung cancers (NSCLCs). Patients with the EML4-ALK fusion gene demonstrate unique clinicopathological and physiological characteristics. Here we present a meta-analysis of large-scale studies to evaluate the clinicopathological characteristics of NSCLC patients harboring the EML4-ALK fusion gene. Methods Both English and Chinese databases were systematically used to search the materials of the clinicopathological characteristics of patients with NSCLC harboring the EML4-ALK fusion gene. Pooled relative risk (RR) estimates and the 95% confidence intervals (95% CI) were calculated with the fixed or random effect model. Publication bias and chi-square test were also calculated. Results 27 retrospective studies were included in our meta-analysis. These studies included a total of 6950 patients. The incidence rate of EML4-ALK fusion in NSCLC patients was found to be 6.8% (472/6950). The correlation of the EML4-ALK fusion gene and clinicopathological characteristics of NSCLC patients demonstrated a significant difference in smoking status, histological types, stage, and ethnic characteristics. The positive rate of the EML4-ALK fusion gene expression in females were slightly higher than that in males, but not significantly (P = 0.52). In addition, the EML4-ALK fusion gene was mutually exclusive of the EGFR and KRAS mutation genes (P = 0.00). Conclusion Our pooled analysis revealed that the EML4-ALK fusion gene was observed predominantly in adenocarcinoma, non-smoking and NSCLC patients, especially those diagnosed in the advanced clinical stage of NSCLC. Additionally, the EML4-ALK fusion gene was exclusive of the EGFR and KRAS mutation genes. We surmise that IHC assay is a valuable tool for the prescreening of patients with ALK fusion gene in clinical practice, and FISH assay can be performed as a confirmation method. These insights might be helpful in guiding the appropriate molecular target therapy for NSCLC.